Rolnicze ubezpieczenia społeczne w Polsce i perspektywy ich zmian - Podstawka, Marian (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1996)
Agricultural social insurance and also employee insurance are not related to the health care system. This system is still functioning through the state health service. Simultaneously the Agricultural Social Insurance Fund does not refund to the state budget the expenses on behalf of health service provided to those insured. Out of the agricultural social insurance one should exclude hired workers employed in agriculture, agriculture entrepreneurs employing hired labour force and members of agricultural co-operatives. The existing principles of financing agricultural social insurance also should be changed. As shown by the experience of western countries a rational solution of this element of the system is to assume a mixed financial index, i.e., capitalisation or redistribution one. This model can be constructed immediately by covering all individual farmers. Then farmers would be obliged to bring into the allocation system a relatively lower fee, simultaneously having a state guarantee concerning the payment of benefits and a voluntary old age premium, which would be subject to capitalisation. The capital shortages at first could be compensated by privatisation revenues or by incurring a public debt.